ANALISIS POTENSI SEKTOR UNGGULAN KOTA BALIKPAPAN DALAM MEMPERSIAPKAN IBU KOTA BARU DARI PERSPEKTIF EKONOMI PERTAHANAN - Yulianti, Nurmaya; Firmansyah, Rizki; Sundari, Sri (MONETER, 2020)
This study aims to determine the leading economic sectors of the Balikpapan City in preparing for the New Capital City of Indonesia. This phenomenon is related to the management of leading sectors in the concept of article defense economy. Where the utilization of leading economic sectors are part of national resources as an effort to improve the standard of living of the people can improve welfare, create security stability and strengthen national defense. This study uses secondary data in the form of Gross Regional Domestic Product (GRDP) of Balikpapan City and East Kalimantan Province in 2016-2018. This research uses a quantitative approach to analyze the data collected. The analytical tools: 1). Location Quotient (LQ) analysis can be used to determine the basis and non-base sectors in the economy of Balikpapan City. 2). Shift Share Analysis is used to determine changes and shifts in the economic structure of the City of Balikpapan. The results of the analysis of 17 sectors based on the two analysis tools show that the leading and potential sectors in the City of Balikpapan are the transportation and warehousing sector; processing industry; information and communication.